Efficacy and Safety of Smoking Cessation Interventions in Patients With Cardiovascular Disease: A Network Meta-Analysis of Randomized Controlled Trials. (January 2017) - Suissa, Karine; Larivière, Jordan; Eisenberg, Mark J.; Eberg, Maria; Gore, Genevieve C.; Grad, Roland; Joseph, Lawrence; Reynier, Pauline M.; Filion, Kristian B.
Abstract : Background—: Although the efficacy and safety of smoking cessation interventions are well established, their efficacy and safety in patients with cardiovascular disease (CVD) remain unclear. The objective of this study was to evaluate the efficacy and safety of pharmacological and behavioral smoking cessation interventions in CVD patients via a meta-analysis of randomized controlled trials. Methods and Results—: EMBASE, PsycINFO, MEDLINE, PubMed, and the Cochrane Tobacco Addiction Specialized Register were searched for randomized controlled trials evaluating the efficacy of smoking cessation pharmacotherapies and behavioral therapies in CVD patients. Outcomes of interest were smoking abstinence at 6 and 12 months, defined using the most rigorous criteria reported. Data were pooled across studies for direct comparisons using random-effects models. Network meta-analysis using a graph-theoretical approach was used to generate the indirect comparisons. Seven pharmacotherapy randomized controlled trials (n=2809) and 17 behavioral intervention randomized controlled trials (n=4666) met our inclusion criteria. Our network meta-analysis revealed that varenicline (relative risk [RR]: 2.64; 95% confidence interval [CI], 1.34–5.21) and bupropion (RR: 1.42; 95% CI, 1.01–2.01) were associated with greater abstinence than placebo. The evidence about nicotine replacement therapies was inconclusive (RR: 1.22; 95% CI, 0.72–2.06). Telephone therapy (RR: 1.47; 95% CI: 1.15–1.88) and individual counseling (RR: 1.64, 95% CI: 1.17–2.28) were both more efficacious than usual care, whereas in-hospital behavioral interventions were not (RR: 1.05; 95% CI, 0.78–1.43). Conclusions—: Our meta-analysis suggests varenicline and bupropion, as well as individual and telephone counseling, are efficacious for smoking cessation in CVD patients. Abstract : Supplemental Digital Content is available in the text.